Macro poverty outlook : country by country analysis and projections for the development world. ([Thimphu] : World Bank group, Poverty Management & Fiscal Management, 2016)
Spring Meetings 2016.
Xerographic copy in a binder.
Keywords: Economic development --Environmental aspects; South Asia --Economic conditions